Detection of st-producing ETEC from watery and formed stools using DNA hybridization and the infant mouse assay - Angeles, Dario Cruz. (1992)
An alkaline-phosphatase conjugated oligonucleotide probe for detecting the heat-stable enterotoxin gene of Escherichia coli was compared with the infant mouse bioassay by examining 360 clinical isolates from stools of PGH patients. Of the 240 E. coli isolates from watery stools, 13 (5.42 ) heat-stable ETEC strains were detected by the probe. While only 1 (0.83 ) was detected by the DNA probe out of 120 E. coli isolates from formed stools. The isolation proportion in watery stools is much higher than in formed stools. Also, a higher percentage of ST-Producing ETEC isolates (6.3 ) were detected from the Pediatric ward. ST-Producing ETEC strains S22 and S64 were questionably positive. While strain S131 showed a negative result for enterotoxin production in the infant mouse assay. In general, most ST-Producing ETEC detected by DNA hybridization which showed intense color deposition also exhibited strongly positive mean ratio of gut to carcass weight values for the infant mouse assay. There was a very good agreement between the 2 methods.
Thesis (Master of Science in Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Eschirichia coli; Hybridization; Stools; Enterotoxins; Etec strains